Efektivitas Biaya Pengobatan Diare Akut Pada Pasien Anak Rawat Inap di Rumah Sakit X - Indrasari, Ferika; Riyadi, Teguh Achmad; Maryeta, Eleonora (Jurnal Farmasi & Sains Indonesia, 2024)
Indonesia in 2021-2022 still obtained a prevalence of 1.3 billion attacks and 3.2 million deaths per year in toddlers due to diarrhoea. Diarrhoea is a disease that kills children under five years of age due to infections that can spread widely in the patient's body. The cost of acute diarrhoea in the hospital is all costs that have been incurred by patients related to medical services. These costs include treatment, medication and laboratory costs. This study aims to determine the Cost Effectiveness of Acute Diarrhoea Treatment in Inpatient Pediatric Patients at Hospital X quantitative data, namely data on pediatric patients with acute diarrhoea from inpatient examinations at Hospital X with Costeffectivinees Analysis (CEA) Research Design which is one of the pharmacoeconomic approaches to determine the comparison of the effectiveness of therapeutic outcomes and the costs of the treatment used. Data collection based on observation sheets (length of treatment, types of drugs used, medical treatment costs, administrative costs, and treatment costs for diagnosis of acute diarrhoea) total cost of acute diarrhoea in inpatient care at X Hospital during July - December 2022. The results of the study on the cost-effectiveness of treatment of acute diarrhoea in paediatric inpatients at Hospital X showed that the use of Orinkz was more effective than the combination of orezinc- nifudiar. Judging from the ACER value of Oriznik of Rp 17,029, - while the combination of orezinc- nifudiar Rp 17,684.